Sky Yogi: Relax and Stretch for a Better Flight. - Yogi, Desk (linkedin.com, 2020)
Relax, stretch, and breathe easy every time you fly. Learn simple exercises to help you wake up your body, fight jet lag, relieve upper-body tension on a cramped flight, and more.